Intelectuais brasileiros em disputa pela Escola Nova na década de 1930 - Celeste Filho, Macioniro [UNESP] (My University, 2013)
In the first decades of the last century, Brazilian intellectuals played an im- portant role in the new configuration to the country reached. Brazil had then passed by rapid process of moderniza- tion. The educational field was place of contention between different currents of intellectuals. The idea was to create a new society through what is called the New School. In Brazil, unlike in Europe, most of the population had no access to school. Therefore, the New School was not privileged to critique existing school system, but the actual construction of the large Brazilian childhood schooling. Thus, we crea- ted libraries in teaching urban school groups, with the aim of improving the training of primary school teachers in the pedagogical ideas of the New School. This work has for objective to understand the conflicts among Brazi- lian intellectuals on the list of recommended readings for teacher training schools in the first half of the twentieth century. This paper presents an exam- ple of this intellectual dispute through the analysis of a Brazilian school li- brary copy of the 1930s.

En las primeras décadas del siglo pasa- do, los intelectuales brasileños ejercían papel prominente en la nueva configu- ración que el país alcanzó. Brasil ha pasado entonces por rápido proceso de modernización. El campo educati- vo fue lugar de disputa entre corrientes distintas de intelectuales. La idea era crear una nueva sociedad a través de la llamada Escuela Nueva. En Brasil, la mayoría de la población no tenía ac- ceso a la escuela. Así que la Escuela Nueva no tuvo el propósito de criticar el sistema escolar existente, pero la construcción en efecto de la educación global de los niños brasileños. Por lo tanto, fueron creadas las bibliotecas pedagógicas en los grupos escolares urbanos, con el propósito de mejorar la formación de los maestros en las ideas pedagógicas de la Escuela Nueva. Este trabajo tiene por objetivo entender los conflictos entre los intelectuales brasileños con respecto a las lecturas reco- mendadas para la formación del pro- fesorado de las escuelas de la primera mitad del siglo XX. Para este propósi- to, presenta un ejemplo de esta disputa intelectual por medio del análisis de una biblioteca escolar brasileña en la década de 1930.
Keywords: Brazilian intellectuals; History of Education; New School; Intelectuales brasileños; Historia de la Educación; Escuela Nueva